Pengaruh Daya Tampung Settling Pond untuk Pengendalian Air Tambang PT Victor Dua Tiga Mega, Barito Utara, Kalimantan Tengah - M. Sohib Prabowo; Harjuni Hasan; Rety Winonazada; Shalaho Dina Devy; Windhu Nugroho (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Settling pond is a mine water control facility used to temporarily store pumped mine water before it is discharged from the mining area. This study aimed to determine the storage capacity of the settling pond, evaluate the effect of pump discharge on its storage capacity, and develop a redesign to prevent overflow at Pit 7, Luwe Site, PT Victor Dua Tiga Mega, North Barito Regency, Central Kalimantan Province. The study employed field measurements of the settling pond geometry, pump discharge measurements using a flowmeter, sediment thickness measurements using the sounding method, and storage capacity analysis based on the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018. The results showed that the settling pond had a geometric capacity of 6,779.50 m³, while the incoming pump discharge reached 23,748.29 m³/day, indicating that the existing capacity was insufficient and had the potential to cause overflow. Based on the evaluation, the recommended pump discharge was 4,541.24 m³/day, accompanied by a redesigned three-compartment settling pond with a storage capacity of 24,400 m³, meeting the required capacity specified in the ministerial regulation.